PELANGGARAN PRINSIP TANGGUNGJAWAB PERUSAHAAN ASURANSI INVESTASI PERSPEKTIF PERUNDANG-UNDANGAN DAN HUKUM EKONOMI SYARIAH - Yoghi Arief Susanto; Yeti Sumiyati (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: The Board of Directors is an organ of the company responsible for the performance of the company, which in its duties must adhere to fiduciary duties, duties of skill and statutory duties. The purpose of this research is First, to review the responsibility of the board of directors of PT. Asabri against high-risk investments based on the laws and principles of Sharia economic law, Second, to review sanctions against violations of the principle of responsibility committed by the board of directors of PT. Asabri for high-risk investments. The method used in this research is normative juridical, analytical descriptive research specification with systematic interpretation data analysis method. The results of this study concluded. First, the responsibility of the board of directors of PT. Asabri is a personal responsibility, and responsibility in a rented way with members of the board of directors of PT. Asabri because of his negligence and indiction violated the principle of responsibility and violated the principle of Sharia economic law, thereby harming the company and having to reimburse a certain amount of losses. Second, sanctions against violations of the principle of responsibility, namely civil sanctions based on articles 1365 and 1366 of the Criminal Code, and criminal sanctions if the actions of the directors do not comply with the principle of responsibility can be ensnared with articles 398 and 399 of the Criminal Code.